THE WAY OF THE WORM - Campbell, Ramsey, Winner of World Fantasy Lifetime and Bram Stoker Awards, 1946- (London : Flame Tree Press, 2022)
The third and final novel in Ramsey Campbell's triumphant Lovecraftian trilogy, The Three Births of Daoloth, where time travel, monstrous evil and the alien apocalypse combine to create a stunning conclusion for streaming TV lovers and suspense readers alike.
Keywords: Cults -- Fiction; Family secrets -- Fiction; Time travel -- Fiction; Good and evil -- Fiction; England -- Fiction; Paranormal fiction; Horror fiction; Science fiction